Brachyopa minima (Diptera: Syrphidae), a new species from Greece with notes on the biodiversity and conservation of the genus Brachyopa Meigen in the Northern Aegean Islands - Pérez-Bañón, Celeste; Radenković, Snezana; Vujić, Ante; Petanidou, Theodora (Zootaxa, 2016)
An on-going study of the hoverfly fauna of the Northern Aegean Islands (Greece) has revealed the presence of four species of the genus Brachyopa Meigen. During the survey the following species were found: B. bicolor (Fallén), B. quadrimaculosa Thompson in Kaplan & Thompson, B. minima Vujić & Pérez-Bañón sp. nov. and an unidentified species very close to B. pilosa (Collin). Morphological characters and mitochondrial COI barcodes were used to link different life stages of B. minima, and to identify a larval specimen of B. bicolor. In this study adult and larval morphology and habitat preferences for B. minima are described. The description of larval morphology of B. bicolor and Brachyopa sp. aff. pilosa is amended too. An identification key to the adults of the B. quadrimaculosa group sensu Kassebeer (2002) in the Eastern Mediterranean (Greece, Israel and Turkey) is provided. The importance of specific microhabitats for the continued existence of these taxa is discussed.